Patients with Chronic Obstructive Pulmonary Disease Suffer from Worse Periodontal Health—Evidence from a Meta-Analysis - Shi, Quan; Zhang, Bin; Xing, Helin; Yang, Shuo; Xu, Juan; Liu, Hongchen (Frontiers in Physiology, 2018)
Background and Objective: It is widely accepted that there is an association between chronic obstructive pulmonary disease (COPD) and periodontitis. However, whether the periodontal status of the COPD patients is worse than that of the non-COPD subjects is seldom assessed. The findings currently available are inconsistent, some even contradictory. Therefore, we performed this meta-analysis to compare the periodontal health status of COPD patients and non-COPD subjects. Methods: PubMed and Embase were searched for all of the eligible studies which comparing the periodontal status between COPD patients and non-COPD subjects. The results of periodontal parameters in each study were extracted and the mean differences and 95% confidence intervals (CIs) for each parameter were calculated to determine their overall effects. Results: In total, 14 studies involving 3348 COPD patients and 20612 non-COPD controls were included and nine periodontal indexes were analyzed. The mean differences (95% CIs) between COPD and non-COPD subjects for probing depth, clinical attachment loss, level of alveolar bone loss, plaque index, oral hygiene index, bleeding index, bleeding on probing， gingival index and remaining teeth were 0.261 (0.020-0.501), 0.480 (0.280-0.681), 0.127 (0.000-0.254), 0.226 (0.043-0.408), 0.802 (0.326-1.279), 0.241 (-0.106-0.588), 6.878 (5.489-8.266), 0.364 (0.036-0.692) and -3.726 (-5.120–2.331), respectively. Conclusion: In summary, this meta-analysis demonstrates that the COPD patients suffer from worse periodontal health status, indicated by deeper periodontal pockets, high level of clinical attachment loss, worse oral hygiene, more inflammation and bleeding in the gingival tissue, and lower number of remaining teeth. Nevertheless, considering the limitations in our meta-analysis, more high-quality and well-designed studies focusing on the periodontal health of the COPD patients are required to validate our conclusion.